A quality improvement plan for hypertension control: the INCOTECA Project (INterventions for COntrol of hyperTEnsion in CAtalonia) - Vallès-Fernandez Roser; Rosell-Murphy Magdalena; Correcher-Aventin Olga; Mengual-Martínez Lucas; Aznar-Martínez Núria; Prieto-De Lamo Gemma; Franzi-Sisó Alícia; Puig-Manresa Jordi; Ma Bonet-Simó Josep (BMC, 2009)
Abstract Background Different studies have shown insufficient blood pressure (BP) control in hypertensive patients. Multiple factors influence hypertension management, and the quality of primary care is one of them. We decided therefore to evaluate the effectiveness of a quality improvement plan directed at professionals of Primary Health Care Teams (PHCT) with the aim to achieve a better control of hypertension. The hypothesis of the study is that the implementation of a quality improvement plan will improve the control of hypertension. The primary aim of this study will be to evaluate the effectiveness of this plan. Methods and design Design: multicentric study quasi-experimental before - after with control group. The non-randomised allocation of the intervention will be done at PHCT level. Setting: 18 PHCT in the Barcelona province (Spain). Sample: all patients with a diagnosis of hypertension (population based study). Exclusion criteria: patients with a diagnosis of hypertension made later than 01/01/2006 and patients younger than 18 years. Intervention: a quality improvement plan, which targets primary health care professionals and includes educational sessions, feedback to health professionals, audit and implementation of recommended clinical practice guidelines for the management of hypertensive patients. Measurements: age, sex, associated co-morbidity (diabetes mellitus type I and II, heart failure and renal failure). The following variables will be recorded: BP measurement, cardiovascular risk and antihypertensive drugs used. Results will be measured before the start of the intervention and twelve months after the start of the study. Dependent variable: prevalence of hypertensive patients with poor BP control. Analysis: Chi-square test and Student's t-test will be used to measure the association between independent qualitative and quantitative variables, respectively. Non-parametric tests will be used for the analysis of non-normally distributed variables. Significance level (α) will be set at < 0.05. Outcomes will be analysed on an intention-to-treat basis. Discussion The implementation of a quality improvement plan might benefit the coordination of different professionals of PHCTs and may also improve blood pressure control. Trial Registration This protocol has been registered at clinicaltrials.gov with the ID number MS: 1998275938244441.